The Midland Sun: Portraying the City of Midland, Michigan, Home of America's Greatest Chemical Institution (1926)
November 1926 issue of The Midland Sun, a weekly periodical published by Frank Burton in Midland, Michigan between 1881 and 1927. In 1927 the publication merged with the Midland Republican (1881-1927) to form the Midland Republican and the Midland Sun (1927-1928). This issue celebrates a decade of growth in the city of Midland, Michigan from 1916-1926. The issue contains articles concerning the various organizations, public facilities, attractions, and advertisements for local businesses. The issue notably contains several articles regarding the Dow Chemical Company including a feature by Herbert H. Dow (1866-1930) titled Why I Came to Midland and the portraits of many Dow Chemical employees.
Keywords: Michigan--Midland; Dow Chemical Company; Dow, Herbert Henry, 1866-1930; Herbert H. Dow House (Midland, Mich.); Employees